Association of grip strength and comorbidities with all-cause mortality in the older hypertensive adults - Wang, Ying; Meng, Tianyu; Yang, Wei; Yan, Miaojia; Su, Xianming; Wang, Xiaohong; Chen, Lihong; Ren, Yanping (Frontiers in Public Health, 2023)
Background: With growing concerns about global population aging, comorbidity, and disability have emerged as key variables that influence the health of the older adults in terms of disease and function. This study sought to examine the impact of comorbidity and impairment using disease and functional status indicators of all-cause mortality in the older adults. Hypertension, which was chosen as the indicator chosen for disease, has the greatest prevalence in the older population. A total of 15 self-reported chronic conditions were added as indicators of comorbidity, and grip strength was chosen as a measure of functional status. The study also evaluated the association between grip strength and comorbidity, as well as its consequences on all-cause death and survival in a hypertensive senior population. Methods: We chose a total of 2990 hypertensive participants aged ≥60 years whose data for grip strength were collected in the National Health and Nutrition Examination Survey conducted between 2011 and 2014. The association of all-cause death with grip strength and comorbidity was examined using a Cox proportional hazard regression model. The interaction between comorbidity and all-cause mortality, as well as its association with grip strength, was also examined. Results: The hazard ratio [95% confidence intervals (CIs)] for all-cause mortality in the highest grip strength tertile was 0.266 (0.168-0.419), compared to the lowest grip strength tertile. The all-cause mortality decreased with an increase in the number of co-morbidities [2.677 (1.557-4.604) in the group with >3 chronic diseases]. The weighted generalized model revealed a negative correlation between grip strength and comorbidities in more than three groups after accounting for all possible variables (β=-2.219，-3.178~ -1.260，p<0.001). The risk of mortality reduced with increasing grip strength in patients with >3 comorbidities (p-value for trend <0.05), but no meaningful difference was found in the interaction between comorbidities and grip strength (p-value for interaction >0.05). Conclusions: In older hypertension patients, grip strength and comorbidities were correlated with all-cause death, and there was a negative correlation between grip strength and comorbidities. Higher grip strength was associated with fewer fatalities in patients with >3 comorbidities, suggesting that functional exercise can improve the prognosis of comorbidities.